The factors that influence a competitive entrepreneur: A study in Kuching City / Masyitah Sarip - Sarip, Masyitah (2015)
Entrepreneurship has been defined as the creation of new enterprise”. It is reflects a new growing awareness that entrepreneurship is a "process of becoming rather than a state of being". The purpose of this study is to identify the factors that influence a competitive entrepreneur - a study of Kuching city. For this study the data analysis used was frequency analysis, descriptive statistic and factor analysis. The finding shows that networking factor is the highest factor that influences a competitive entrepreneur. Meanwhile, the lowest factors that influence a competitive entrepreneur were innovation or venturesome factor. Accordingly there a recommendations that is suggested for this research.